Bibliometrijska analiza Zbornika gozdarstva in lesarstva: 1950-2004 - Božič, Maja (Zbornik gozdarstva in lesarstva, 2005)
Bibliometric methods are a quantitative method of measuring characteristics ofpublished articles with which new knowledge about the scientists' work is acquired The article presents the results obtained by bibliometric analysis ofthe journal "Research reports: Forestry and Wood Science Technology", in which 593 articles published in it since its beginnings in 1950 until 2004 were processed. The analysis embraced the number of articles in separate years, number of authors, citations, self-citations and the structure of articles with tables and figures. Separate articles are usually written by less than two authors, most of them (68 %) employed by the three journal's publishing institutions. Only 17 % of the authors are females. The average number of quotations is 23, 2 of which are self-citation; they are provided with 3 - 4 tables and 4 - 5 figures. In 91 %, the articles are written in Slovene language. From the beginning of the journal's existence, Slovene references have remained the primary source of literature (34 %), 24 % of which have been published in the journal itself, in the "Slovenian Journal of Forestry", or in the collection "Professional and scientific works". In the early 1990s, English sources superseded those written in German.
Keywords: bibliometrija; citiranost; Zbornik gozdarstva in lesarstva; znanstveno delo